Effect of natural deep eutectic solvents on properties of micro crystalline cellulose isolated from kenaf fibre - Meraj, Aatikah; Jawaid, M.; Pratap Singh, Surendra; Nasef, Mohamed Mahmoud; Ariffin, Hidayah; Mohamad Haafiz, M.K. (Elsevier, 2023)
Natural deep eutectic solvents have gained popularity due to their environmentally benign, recyclable, and reusable properties. They can be used many times without losingtheir effectiveness. Therefore, natural deep eutectic solvents used as effective reagent for lignocellulosic biomass pre-treatment for lignin removal. In this work, the natural deep eutectic solvents (i.e., Lactic Acid: Choline Chloride) is used to treat the kenaf fibre biomass with a molar ratio of 2:1 and then microcrystalline cellulose was obtained through acid hydrolysis. The analytical analysis of kenaf microcrystalline cellulose was investigated through Infrared fourier transform spectroscopy, X-ray Diffraction, thermogravimetric analysis, particle size distribution analysis, and scanning electron microscopy. The fourier transform infrared spectroscopy analysis result showed that the maximum proportion of lignin and partial hemicellulose from kenaf fibre were removed during natural deep eutectic solvents pre-treatment. Kenaf microcrystalline cellulose X-ray diffraction results revealed higher crystallinity at 78° compared to other peaks. The thermal analysis shows the kenaf microcrystalline cellulose thermal stability , making it suitable material for more desirable application in many areas. We concluded from obtained results that microcrystalline cellulose extracted with natural deep eutectic solvent pre-treated kenaf fibre can be used in various cellulosic material development in the future for the food packaging, tissue culture, paper, automotive, biomedical, and pharmaceutical applications.